The effectiveness of fermented mixed tofu industry and restaurant wastes addition on peat water that is used as Chlorella sp. culturemedia - Michael Halomoan Sihombing; Budijono Budijono; Sampe Harahap (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTPeat water has a low nutrient content, but it can be enriched by addition of fermented mixed tofu industry and restaurant waste. This media may be used for growing  Chlorella sp. This study aims to determine the effect offermented mixed tofu industry and restaurant waste addition as alternative nutrients for the growth of Chlorella sp. This study was conducted in September-Oktober 2019.RAL method was applied with 6 different concentrations of mixed solution (50% tofu industry waste + 50% restaurant waste), there were600 ml/3L (P1), 1,200 ml/3L(P2), 1,800 ml/3L (P3),2,400 ml/3L(P4) and 0 ml/3L (P5), with 3 repetitions.Each experimental unit was added with 75ml of Chlorella sp (106 cells/L). and was cultured for 7 days. Results shown that Chlorella sp. grow well in all treatments, except control.The best result was provided by P4 (8.531 x 106 cells/ml)that was achieved on the 5th day. The highest dry Chlorella sp. biomass was 4.30 g/L, around 84.2% of wet weight. Based on data obtained, it can be concluded that the peat water can be enriched by addition of fermented mixed tofu industry and restaurant wastesand it can be used as nutrients for growing Chlorella sp.Keywords: organic matters, algae culture, microalgae, liquid waste, alternative nutrient